Pengembangan Aplikasi Kelas Digital Scola sebagai Media Evaluasi Pembelajaran Musik di Sekolah - Lanang Riyadi; Yudi Sukmayadi (Institut Seni Indonesia Denpasar, 2023)
Purpose: The use of media in the learning evaluation stage affects student learning outcomes which can be seen from scores in tests and other evaluation stages. It is also seen from how the ability of educators to create learning media that can develop students' interest in the learning process to evaluate learning which is expected to make the stages of learning more effective and efficient with the use of attractive teaching media. One of the interesting learning media is the Digital Classroom application by Scola LMS (Learning Management System) also as a digital learning solution in schools. Method: By utilizing the Scola application, educators can also manage school data in an organized and centralized manner, access content and materials from other schools, and make learning interactive. Result and discussion: This research uses the 4D development model which is formed of the stages of define, design, develop, and disseminate by focusing on the definition and design stages of application development. Implication: The results show that the Digital Classroom Application by Scola is a solution to answer the challenges of conventional learning that is so-so so as to create a digitally sophisticated learning atmosphere.